Design of Coconut Milk Pressing Machine with Two Screw Shafts to Improve Extraction Efficiency and Quality - Setiawan, Angga; Wijaya, Rahmat; Subeno, Agus; Budi Affandi, Arif; Okviyanto, Toni; Mubina Dewadi, Fathan (Universitas Negeri Jakarta, 2026)
Coconut milk pressing machines play an important role in coconut processing; however, conventional single-screw designs still face limitations related to pressure distribution and extraction stability. This study aims to design and analyze a coconut milk pressing machine, employing a counter-rotating two screw shafts configuration as an alternative to commonly used single-screw systems. The research methodology includes a reverse-engineering approach, analytical calculations to determine pressing capacity, power, torque, and pressure, and finite element analysis (FEA) simulations to evaluate the structural strength of main components. The analytical results indicate that the proposed design achieves a theoretical pressing capacity of 53 kg/h, with a shaft power requirement of 1.11 kW and a pressing pressure of 1.67 × 10⁵ N/m². FEA results show that the Von Mises stress and deformation remain below the allowable limits of the selected material, indicating a conservative, structurally safe design. All results presented in this study are theoretical and numerical in nature and have not yet been validated through experimental testing. The novelty of this work lies in the application of a counter-rotating two screw shafts configuration, which theoretically provides a more uniform pressure distribution than conventional single-screw systems without a significant increase in power consumption. Future work will focus on prototype fabrication and experimental testing to validate extraction performance, energy efficiency, and hygienic aspects.